(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article discusses the issues of developing the creative (creative) abilities of primary school students. Creative thinking is an important factor in the formation of a successful personality in today’s rapidly changing world. The article discusses the theoretical foundations of the concept of creative skills, pedagogical and psychological conditions for their development, as well as practical methods